Bridging The Gap in School Leadership: Developing Management Competence and Supervisory Strategies for Improved Teacher Effectiveness - Adrian G Refugio; Joseph G Refugio; Sheila S Dalumpines (Research Synergy Foundation, 2025)
Inadequate leadership can impede teachers' effectiveness and diminish the quality of education. This study delves into the influence of management competence and supervisory strategies on teachers' performance to unlock their potential for delivering quality education. Using a descriptive-correlational research design and a questionnaire checklist, we investigated the relationship between these variables across fourteen public schools in Dipolog City. Our findings revealed that while most administrators were highly competent, factors such as age, experience, and educational qualifications influenced performance in specific areas. Surprisingly, the number of training sessions attended did not significantly impact competence. Administrators frequently utilized classroom visitation and demonstration strategies, revealing a strong positive correlation between their level of competence and the implementation of these supervisory approaches. However, no significant relationship was found between administrators' competence and teacher performance, indicating the need for further investigation into factors affecting teachers' effectiveness.